Mask of Power Senior Student Power Hmps Pips in LDKM New Students of PIPS Faculty of Social and Law Sciences State University of Makassar - Dewi Reca Litha (Jurnal Indonesia Sosial Teknologi, 2024)
This study aims to analyze the construction work of senior students in the LDKM of new PIPS students and analyze the factors of the construction of senior students in the LDKM of new students of PIPS. To achieve the objectives of the study, Heidegger used a Phenomenology-Hermeneutics research approach. These research data were obtained through participatory observation, non-intervention strategies, non-structural interviews, and documentation. The data were analyzed using interpretation analysis methods and Nvivo data analysis program version 12. The results showed (1) The construction work of HMPS PIPS senior students in LDKM (Basic Leadership Training) activities began with a narrative of skills, skills, leadership, agents of change, the title of God, and students who have. The presence of this ideal fantasy (object a) makes them participate in LDKM (Basic Leadership Training) activities in which they are dominated through the path of requiring an understanding of the materials in LDKM (Basic Leadership Training), which are covered with symbolic violence that works through euthanizations leading to psychological and physical violence as a closure. (2) The working factor of HMPS PIPS senior students in LDKM (Basic Leadership Training) activities because it maintains the existence of the HMPS PIPS internal institution to compete for the position of President of BEM (Student Executive Board) from the Faculty to University level, where HMPS PIPS senior students, especially alums, get pride and recognition as senior figures who create PIPS new student cadres (maba) who can occupy as President BEM (Student Executive Board).